International Chinese postgraduate students' adaptation strategies for oral English communication practices in Malaysian higher education institutions - Zhai, Xiuwen; Razali, Abu Bakar (Hindawi, 2022)
Since establishing the Silk Road initiatives, increasing numbers of Chinese students are going to Malaysia to pursue their postgraduate degrees. As the largest group of international students, numerous research studies have reported that Chinese international postgraduate students face language obstacles in English language communication during their overseas studies in English-medium instruction (EMI) campuses. This qualitative case study supplies in-depth insight into different adaptation strategies utilized by international Chinese postgraduate students to overcome challenges faced in academic communication practices. Qualitative data were collected from three sessions of semistructured in-depth interviews. Informants were six international Chinese mainland postgraduate students (i.e., three masters’ students, three Ph.D. students) from diverse disciplines. The interviews allowed the participants to share their own experiences of utilizing effective adaptation strategies to overcome challenges faced in academic English communication practices in their studies. Their adaptation strategies include enhancing their oral English language communication competence and academic achievement. Thus, this study contributes by providing suggestions to Malaysian higher education institutions seeking measures to improve international service quality.